Effects of smoking shisha, cancer risk, and strategies for prevention of shisha habit - Shankargouda Patil; Amit Vasant Mahuli; Saman Warnakulasuriya (Elsevier, 2022)
Smoking tobacco through a water pipe, also referred to as Shisha, is prevalent in Middle Eastern countries but has gained popularity worldwide, especially among youth. The increasing global trend of shisha use is mainly led by misleading information about it being safe. The shisha smoke has potentially harmful chemicals, including several human carcinogens and other toxic products. There are recognised adverse effects on passive smokers exposed to second-hand smoke. It is a potential risk factor for several cancers and risks pregnant women and the foetus. A session of shisha smoking for 40 minutes is equivalent to smoking 100 or more cigarettes. There should be awareness about Shisha's harmful effects to reduce the risk to health through a coordinated global effort.